Love in Aladdin Movie Directed by Guy Ritchie - Unpris Yastanti; Faridatul Hasanah; Anggraini Anggraini; Lia Nurmalia (LPPM Universitas Bina Sarana Informatika, 2022)
Love is an emotion or positive feeling like affection, sacrifice, and trust contained in human beings aimed at other human or other objects that are around it. In other words, love is sharing affection, struggle, and complement each other. The purpose of this research are to identify characteristics of love, types of love, and moral message in Aladdin Movie directed by Guy Ritchie. This research used descriptive qualitative method to analyze the data. The data are the scenes and the dialogs of the main character that contains the characteristic of love, types of love. The result of this study reveal that: (1) There are 3 characteristics of love in Aladdin movie, they are trust, healing, and teamwork. (2) There 7 types of love in Aladdin movie, there are eros, philia, storge, agape, ludus, pragma, and philautia. (3) The moral message contained in the movie; the true love has their ways to find their soul. Aladdin falling in love with Princess Jasmine. Although, there are a lot of problems and in difficult condition, finally, Aladdin got the Princess Jasmine’s love.